2017
DOI: 10.5758/vsi.2017.33.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Assisted Laparoscopic Nephrectomy and Auto-Transplantation for a Hilar Renal Artery Aneurysm: A Case Report

Abstract: A 52-year-old man was admitted with an incidentally detected right renal artery aneurysm (RAA). Computed tomographic angiography with three-dimensional reconstruction revealed that the aneurysm was 2.2 cm in diameter and located at the renal hilum. We performed hand-assisted laparoscopic nephrectomy with ex vivo repair of the RAA and auto-transplantation with minimal elongation of Gibson incision. The operation and postoperative course were uneventful. At last follow-up, the patient was alive with a well-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Open repair techniques include in situ excision and bypass (REB), ex vivo repair and auto-transplantation (RAT), and nephrectomy. Finally, type III RAAs are located at the hilum or intraparenchymal, and the open repair techniques have the absolute indication [ 9 , 10 , 17 , 18 ]. However, considering the advancement in both endovascular experience and equipment in preserving even small splanchnic branches, we believe that the endovascular approach should always be in our operational treatment algorithm [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open repair techniques include in situ excision and bypass (REB), ex vivo repair and auto-transplantation (RAT), and nephrectomy. Finally, type III RAAs are located at the hilum or intraparenchymal, and the open repair techniques have the absolute indication [ 9 , 10 , 17 , 18 ]. However, considering the advancement in both endovascular experience and equipment in preserving even small splanchnic branches, we believe that the endovascular approach should always be in our operational treatment algorithm [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported cases, four patients had a solitary kidney, two patients were pregnant, and two repaired kidneys were successfully transplanted to two men, respectively, which provided benefits to both donors and recipients. 5 , 8 , 10 , 11 , 13 19 After analysis of the therapeutic strategies, we found that 47% ( N = 26) of HRAAs were treated by ex vivo reconstruction (EVR), 44% ( N = 24) were treated by in situ reconstruction (ISR), 5% ( N = 3) were treated by endovascular therapy, and 4% ( N = 2) were treated with nephrectomy. Laparoscopy was used to reduce surgical trauma owing to its lower invasiveness, and 17% ( N = 9) of the operations were performed with the aid of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Open approaches are possible in up to 96% of cases, and these approaches not only eliminate the risk of rupture of the aneurysm but also may improve renovascular hypertension. 1,[10][11][12][13] One question that remains unanswered in the literature is whether transplanting a graft with a repaired aneurysm will place the recipient on immunosuppressive therapy at risk for the development of these lesions in the remaining native artery during the long-term period. It is known that cardiovascular risk factors might be potentiated by immunosuppression; however, there is no relationship described between the use of immunosuppressive therapy and growth rate of the RAA.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Open approaches are possible in up to 96% of cases, and these approaches not only eliminate the risk of rupture of the aneurysm but also may improve renovascular hypertension. 1,10 13…”
Section: Discussionmentioning
confidence: 99%